LEGAL LIABILITY ON ADMINISTRATIVE TORT: RECENT REGULATION PERSPECTIVE - Muhammad Farizka Sisma; Zakki Adlhiyati (STIH Putri Maharaja, 2023)
The development of judicial power brings some changes. One of them is the evolution of administrative law related to the object of administrative dispute, which embraces concrete action. Thus, the administrative tort was also affected by this change. This writing aims to understand the government's liability on the administrative tort and the regulation of onrechtmatige overheidsdaad before and after the enactment of Law Number 30/2014 on government administration. The normative juridical method reveals that the origin of authority plays a pivotal role in deciding the government's liability. Initially, the article of 1365 Civil Procedural Law was the legal based of an administrative tort, but in 2014 it was also stipulated in the Government Administration Law. In addition, The Law of Government administration broadens the limitation of administrative decisions and allows the administrative court to examine the administrative tort legally.